Static Shear Strength of Double-Strap and Single-Lap Joints incorporating Toughened Mussel Epoxy - Azhar, Muhamad Nur Syahrin; Velayutham, Subashini; Sugiman, Sugiman; Desmond Daniel Chin,; Lee, Sim Yee; Goh, Ren Han; Mohd Hilton Ahmad, (International Journal of Sustainable Construction Engineering and Technology, 2024)
Structural integrity requires proper joining types and resistance to the applied load. Adhesively bonded joints are broadly classified into two types: lapped joints and strap joints, favoured for their low weight penalty, and less stress concentration, albeit requiring meticulous surface preparations. In light of increasing environmental awareness, material researchers worldwide are substituting synthetic reinforcing fibre in Fibres-Reinforced Polymer (FRP) production with natural fibre such as Kenaf Fibres-Reinforced Polymer (KFRP). Moreover, the low shear strength in neat epoxy resin, commonly used as a matrix binder in composite material productions, can be further enhanced by adding fillers, usually with commercial fillers. Food waste, such as mussels, contains substantial calcium carbonate content and has a promising potential as a replacement for commercial fillers. Therefore, further research is required to assess the joining performance and associated joining strength of using kenaf fibre with toughened mussel powder as joining plates, either adhesively bonded in strapped or lapped joints. In this study, the static shear strength of double-strapped joints was examined with varying KFRP lengths of 20, 30, 40, 50, and 60 mm. Additionally, single-lap joints were tested using neat epoxy resin incorporated with mussel powder, with lengths varied at 30, 40, and 50 mm. The Universal Testing Machine (UTM) with a crosshead speed of 0.5mm/min was used to test all specimens. It was found that longer overlap length (in lap joints) or longer KFRP lengths were associated with better joint strength. All testing specimens of strapped joints failed in FRP rupture, indicating that the effect of KFRP length is less pronounced than the overlap length in lap joints. The lap joint demonstrated a notable improvement in joint strength, with a 64% enhancement observed in cases with a 50 mm KFRP overlap length, and a 66% enhancement for strap joints with a 60 mm KFRP overlap length. Despite good joint strength were observed in both joint types, other parametric studies including KFRP thickness and the incorporation of other waste fillers in neat epoxy resin can be varied.